Pengaruh Dimensi Marketing Communication Terhadap Brand Loyalty pada Penjualan Skincare di Indonesia - Setiawan, Donny; Riorini, Sri Vandayuli; Andhika, Raihan; Benedick, Julio (Abdimas Indonesian Journal, 2025)
Skincare is a variety of skin care products such as facial cleansers, moisturizers, serums, and masks, increasingly popular among Indonesian consumers due to the increasing awareness of the importance of good skin care. This study aims to test and analyze the effect of Advertising on Brand Loyalty, Public Relations on Brand Loyalty, Direct Marketing on Brand Loyalty, Sales Promotion on Brand Loyalty on Skincare in Indonesia. The sampling procedure used in this study to collect relevant data is by using a questionnaire. A total of 170 samples were collected and the method in this study used the purposive sampling method. Data were analyzed using the SEM (Structural Equation Modeling) and AMOS (Analysis of Moment Structure) methods. The results of this study indicate that there is no positive influence between Advertising on Brand Loyalty, there is a positive influence between Public Relations on Brand Loyalty, there is no positive influence between Direct Marketing on Brand Loyalty, there is a positive influence between Sales Promotion on Brand Loyalty.